Modern broiler chickens exhibit a differential gastrointestinal immune and metabolic response to repeated CpG injection relative to a 1950s heritage broiler breed - Aylward, Bridget A.; Johnson, Casey N.; Perry, Famatta; Whelan, Rose; Arsenault, Ryan J. (Frontiers in Physiology, 2024)
The Athens Canadian Random Bred (ACRB) heritage broiler breed, which has not been selectively bred since the 1950s, is a point of comparison to the modern-day broiler and could highlight potential genetic-derived differences in immune responses. To observe the modern and heritage birds' immune responses in action, the innate immune ligand CpG oligonucleotides were administered at multiple time points through the birds' lives from the day after hatch to day 35 post-hatch. This study allowed for the observation of changes in metabolic and immune signaling in response to repeated injections of a known Toll-like receptor (TLR) ligand, CpG. Jejunum and cecal tonsil samples at multiple time points during grow out were collected and used for kinome array analysis to measure kinase activity in immunometabolic signaling pathways in the gut tissue. In addition cytokine gene expression was measured in these tissues. The modern birds' response to the treatment was more innate and showed evidence of metabolic energy shift. The heritage birds' response to the treatment was adaptive, with metabolic changes indicative of a well-regulated response. Overall, the results from this study suggest that modern broiler chickens do not adequately balance resources between growth and immune responses during an immune challenge, and this deficit is most evident around the two-week post-hatch time point. This is a critical time for these birds, as their muscle deposition continues to accelerate, and they are vulnerable to disease challenges. Ideally, future work can clarify the reason for this response discrepancy in the modern broiler and therapeutic interventions to rescue this phenotype could be elucidated.